Technologies of birth and models of midwifery care - Christine McCourt (SciELO, 2014)
This article is based on a study of a reform in the organisation of maternity services in the United Kingdom, which aimed towards developing a more woman-centred model of care. After decades of fragmentation and depersonalisation of care, associated with the shift of birth to a hospital setting, pressure by midwives and mothers prompted government review and a relatively radical turnaround in policy. However, the emergent model of care has been profoundly influenced by concepts and technologies of monitoring. The use of such technologies as ultrasound scans, electronic foetal monitoring and oxytocic augmentation of labour, generally supported by epidural anaesthesia for pain relief, have accompanied the development of a particular ecological model of birth - often called active management -, which is oriented towards the idea of an obstetric norm. Drawing on analysis of women's narrative accounts of labour and birth, this article discusses the impact on women's embodiment in birth, and the sources of information they use about the status of their own bodies, their labour and that of the child. It also illustrates how the impact on women's experiences of birth may be mediated by a relational model of support, through the provision of caseload midwifery care.